Novel pathway of chalcopyrite formation at low temperature in microenvironments of acidic, metal-rich sediments - Sánchez Andrea, Irene; Li, Zhiquan; Ilin, Andrey M.; Yusta, Iñaki; Ilyn, Maxim; Martinez-Amesti, Ana; van der Graaf, Charlotte; Scheinost, Andreas; Prieur, Damien; Sorrentino, Andrea; Oliete, Robert; Hao, Weiduo; et al. (Nature Publishing Group, 2025)
Chalcopyrite (CuFeS2) is the main source of copper worldwide and is usually formed at high temperature. Its occurrence at low temperature is poorly documented, and the mechanisms controlling its formation remain uncertain. We found evidences of chalcopyrite formation in acidic pit lake sediments at ~ 12 °C. Using high-resolution electron microscopy and synchrotron-based spectroscopy, we observed aggregates of nanoscale crystals with the composition and structure of disordered chalcopyrite. Laboratory incubations at 20 °C and geochemical modelling suggest that microbial activity may contribute to chalcopyrite formation under these conditions. Particularly, crystal growth was associated with hollow structures resembling microbial cell surfaces, and on the membranes of eukaryotic-like cells, providing nucleation sites. Our findings suggest that microbial processes, including the production of hydrogen sulfide and the presence of organic surfaces, promote chalcopyrite formation at low temperature. This has implications for understanding copper and sulfur cycling and its potential biotechnological application in sulfidic environments.
Keywords: biotechnology; chalcopyrite; electron microscopy; high temperature; hydrogen sulfide; incubation; lacustrine deposit; low temperature; nucleation; 25 Ciencias de la Tierra y del Espacio; ODS 9 - Industria, innovación e infraestructura